PENGARUH METODE KANGAROO MOTHER CARE (KMC) DENGAN PENINGKATAN BERAT BADAN DAN STABILITAS SUHU TUBUH BBLR DI RSUD dr. H. MOCH. ANSARI SALEH BANJARMASIN - Sari, Dina Aulia; Salmarini, Desilestia Dwi; Meldawati, Meldawati; Yuliana, Fitri (Jurnal Delima Harapan, 2024)
Background: Low birth weight (LBW) babies are babies whose birth weight is less than 2500 grams. Problems that may arise in LBW cases include unstable body temperature, respiratory problems, digestive and nutritional disorders, weak suction reflex, intestinal morbidity which results in decreased body weight, liver immaturity, anemia, seizures, infections, hypoglycemia, hyperglycemia and hypocalcemia. The intervention that can be carried out is the use of the kangaroo mother care (KMC) method. The KMC concept imitates the way kangaroos store their babies in a pouch on their stomachs, allowing heat to flow from the mother's body to the baby kangaroo so that it stays alive and avoids hypothermia. Objective: This study aims to analyze the effect of the KMC method on increasing body weight and stability of LBW body temperature at RSUD dr. H. Moch. Ansari Saleh Banjarmasin. Method: This quantitative research uses a pre-experimental design with one group pretest-posttest. The sampling technique used purposive sampling and obtained 15 respondents. Data analysis uses 2 types of tests. Paired sample T-Test was used to analyze LBW body weight before and after KMC method treatment because the data was normally distributed. Meanwhile, the Wilcoxon test was used to analyze the effect of LBW body temperature before and after KMC treatment because the data was not normally distributed. Results: Analysis of the effect of LBW body weight before and after KMC method treatment obtained a p-value of 0.000. The p-value in the test for the effect of LBW body temperature before and after KMC treatment was found to be 0.001. Conclusion: Looking at the existing results, it can be seen that there is a p value of less than <0.05, meaning that there is a significant difference in the data in the positive direction or an increase before and after the KMC method treatment for both the weight variable and the stability of LBW body temperature at RSUD dr. H. Moch. Ansari Saleh Banjarmasin. Based on these results, it was concluded that there was an influence between the KMC method and increasing body weight and stability of LBW body temperature at RSUD dr. H. Moch. Ansari Saleh Banjarmasin